1983
DOI: 10.1164/arrd.1983.128.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-related Acute Lung Injury Associated with Passive Transfer of Antileukocyte Antibodies1,2

Abstract: Acute lung injury (ALI) is an infrequently recognized complication of transfusion therapy. Although the role of passive transfer of leukoagglutinating antibodies has been acknowledged, there is little documentation of the relationship of these antibodies in transfused blood to the human leukocyte antigen (HLA) phenotype of the recipient. Recently, we observed 5 cases of transfusion-related ALI, and in all cases leukoagglutinating and lymphocytotoxic antibodies were found in serums of the transfused blood produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
265
2
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(275 citation statements)
references
References 0 publications
1
265
2
6
Order By: Relevance
“…[1][2][3][4] TRALI is defined as the acute onset of hypoxia and bilateral pulmonary infiltrates, in temporal relation to a blood transfusion. 1,5 Although the absence of specific disease markers and diagnostic tests has resulted in a large variation in estimations of incidence, 1,[6][7][8][9][10][11][12][13][14] TRALI is generally considered to be a rare event. However, TRALI is underdiagnosed and under-reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] TRALI is defined as the acute onset of hypoxia and bilateral pulmonary infiltrates, in temporal relation to a blood transfusion. 1,5 Although the absence of specific disease markers and diagnostic tests has resulted in a large variation in estimations of incidence, 1,[6][7][8][9][10][11][12][13][14] TRALI is generally considered to be a rare event. However, TRALI is underdiagnosed and under-reported.…”
Section: Introductionmentioning
confidence: 99%
“…Two distinct mechanisms have been suggested for the "second event": the traditional theory proposes an antibody-mediated reaction between recipient neutrophils and antineutrophil antibodies from donors who were sensitized during pregnancy (multiparous women) or by previous transfusion. 7,15,20 An alternative mechanism involves accumulation of bioactive lipids (lysophosphatidylcholines [lysoPCs]) during storage of cell containing blood products. [21][22][23] Cardiac surgery patients may be at risk for TRALI.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a relationship between platelet age and TRALI. Antileukocyte antibodies, activation of the compleman cascade, neutrophil (PMN)-mediated lung injury and pulmonary leukostasis are responsible for the pathogenesis of TRALI [6][7][8]. Furthermore, IL-6 and IL-8 are essential cytokines which stimulate PMN and play important role in pathogenesis of TRALI [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Different from acute respiratory distress syndrome which are caused by other reasons, patients with TRALI recover quickly with resolution of pulmonary infiltrates within 96 h of the transfusion. The mortality rate ranges from 5 to 10 % [6,12]. It was observed that pulmonary infiltration disappeared just after the 18 h of ventilatory support and transfusion, and full recovery was observed after the patient was extubated.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases require oxygen support and mechanical ventilation (1). TRALI was first described as a specific transfusion reaction in 1983 by Popovsky et al (2). According to a United States Food and Drug Administration report on transfusion-related deaths (3), TRALI was the top-ranked cause of reported fatalities (n=127; 48%) from 2005 through 2009.…”
mentioning
confidence: 99%